Outcome of albendazole therapy in the management of hepatic hydatid disease - Bari, Shams Ul; Naqash, Mohd Mubarik; Malik, Ajaz A. (International Journal of Research in Medical Sciences, 2017)
Background: The treatment modalities for managing patients with hepatic hydatidosis include surgical treatment and non-surgical treatments. The non-surgical methods include albendazole therapy and percutaneous management. Use of albendazole as an adjuvant therapy to surgery has been found to significantly reduce the viability of daughter cyst and recurrence of hydatid disease. The aim of the study was to understand the effect of albendazole therapy on the viability of protoscoleces and recurrence rate of hydatid disease of liver. Methods: The study was conducted at Sher-i-Kashmir Institute of Medical Sciences and Medical College, Srinagar, Kashmir India, from March 2010 to February 2012 with further follow up of 3-4 years and the total of 64 patients were studied. ; Patients were divided into two groups, Group A and Group B, each comprising of 32 patients. In group A, patients were given albendazole for 12 weeks preoperatively followed by further postoperative course for 12 weeks. In group B, patients were first taken for surgery followed by postoperative course of albendazole for 12 weeks. The two main outcome measures studied and compared during present study were the viability of the hydatid cysts and the recurrence rate in two groups. Results: Out of those, patients who received preoperative albendazole, 9.37% had viable cysts at the time of surgery as compared to 96.87% of patients who did not receive any preoperative albendazole. In those patients who received only postoperative albendazole therapy, recurrence rate was 18.75% while as there was no recurrence was in patients who received both preoperative and postoperative albendazole therapy. Conclusions: Study concludes that albendazole is safe and effective adjuvant therapy in the treatment of hydatid liver disease.